Development of a finger dummy for contact safety assessment by investigating the dimensions and mechanical characteristics of human fingers - Fengyu Li; Haruki Wada; Ken'ichi Koyanagi; Toru Oshima; Takuya Tsukagoshi; Kentaro Noda (SICE Journal of Control, Measurement, and System Integration)
In the investigation of contact safety assessment of collaborative work between robot systems and humans, the development of a sensor-equipped human dummy is a viable approach for obtaining the internal distribution of strain or stress. It is considered necessary to develop a dummy that faithfully replicates human mechanical characteristics. This paper presents the design and construction of a finger dummy that replicates the dimensions and mechanical characteristics of the human finger. Ultrasound technology is employed to gauge the soft tissue thickness, enabling determination of previously unknown phalanx dimensions. The research also delves into the investigation of the coefficient of friction and elastic property to approximate the human finger. Various surface treatment techniques are used to adjust the friction coefficient. Furthermore, the elasticity of the improved palm dummy samples is assessed based on the strain–stress relationship. These mechanical characteristics were effectively optimized through a meticulous comparison of the measurement results obtained from both the dummy samples and actual human fingers.